Cohort profile: the STOP HIV/AIDS Program Evaluation (SHAPE) study in British Columbia, Canada. Issue 5 (12th May 2020) - Bever, Andrea; Salters, Kate; Tam, Clara; Moore, D M; Sereda, Paul; Wang, Lu; Wesseling, Tim; Grieve, Sean; Bingham, Brittany; Barrios, Rolando
Abstract : Purpose: The Seek and Treat for Optimal Prevention of HIV/AIDS (STOP HIV/AIDS) Program Evaluation (SHAPE) study is a longitudinal cohort developed to monitor the progress of an HIV testing and treatment expansion programme across the province of British Columbia (BC). The study considers how sociostructural determinants such as gender, age, sexual identity, geography, income and ethnicity influence engagement in HIV care. Participants: Between January 2016 and September 2018, 644 BC residents who were at least 19 years old and diagnosed with HIV were enrolled in the study and completed a baseline survey. Participants will complete two additional follow-up surveys (18 months apart) about their HIV care experiences, with clinical follow-up ongoing. Findings to date: Analyses on baseline data have found high levels of HIV care engagement and treatment success among SHAPE participants, with 95% of participants receiving antiretroviral therapy and 90% having achieved viral suppression. However, persistent disparities in HIV treatment outcomes related to age, injection drug use and housing stability have been identified and require further attention when delivering services to marginalised groups. Future plans: Our research will examine how engagement in HIV care evolves over time, continuing to identify barriers and facilitators for promoting equitable access to treatment and care among people living with HIV. A qualitative research project, currently in the formative phase, will compliment quantitative analyses by taking a strengths-based approach to exploring experiences of engagement and re-engagement in HIV treatment among individuals who have experienced delayed treatment initiation or treatment interruptions.